1992
DOI: 10.1111/j.1365-2265.1992.tb02903.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel variant of growth hormone (GH) insufficiencyfollowing low dose cranial irradiation

Abstract: A novel form of GH insufficiency has been observed after low dose irradiation in childhood in which an abnormality of periodicity and a quantitative reduction in GH secretion appears restricted to puberty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
3

Year Published

1993
1993
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 23 publications
0
37
3
Order By: Relevance
“…We did not measure growth hormone secretion in our patients. However, since growth hormone insufficiency (neurosecretory dysfunction) after cranial irradiation in the context of an ALL therapy has already been demonstrated by several investigators [23], this can also be assumed in our irradiated patients. Insufficient growth hormone secretion would explain two observations made in our irradiated patients: it alters the patients’ body composition, which in turn may influence their physical activity; and it can lead to a decrease in RMR as recently reported in patients with growth hormone insufficiency after discontinuation of growth hormone therapy [24].…”
Section: Discussionmentioning
confidence: 99%
“…We did not measure growth hormone secretion in our patients. However, since growth hormone insufficiency (neurosecretory dysfunction) after cranial irradiation in the context of an ALL therapy has already been demonstrated by several investigators [23], this can also be assumed in our irradiated patients. Insufficient growth hormone secretion would explain two observations made in our irradiated patients: it alters the patients’ body composition, which in turn may influence their physical activity; and it can lead to a decrease in RMR as recently reported in patients with growth hormone insufficiency after discontinuation of growth hormone therapy [24].…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, general agreement that cranial XRT with 24–25 Gy is a potent cause of GH insufficiency. The 18-Gy data are more contentious in that Crowne et al [19] showed a quantitative reduction in GH secretion which was confined to the pubertal phase of childhood, associated with a disturbance in the periodicity of GH secretion. Lannering et al [20] confirmed the reduction in GH secretion during puberty, but observed that, in addition, it was present during prepubertal life, whilst, at the same time, they observed no qualitative abnormality in the pattern of GH secretion at any time.…”
Section: Cranial Irradiation and Chemotherapymentioning
confidence: 99%
“…7,8,10 The prevalence of obesity at ®nal height in the survivors of ALL is approximately 4 ± 5 times that expected, 10 ± 12 and this may underestimate the magnitude of the problem since standard weight for height indices underestimate prevalence of excess adiposity. 4,13 Corticosteroids 9 and growth hormone insuf®-ciency following low-dose cranial irradiation (where it is still used 14 ) might contribute to excess weight gain in ALL, but the major cause of obesity on modern treatment protocols has recently been identi®ed as reduced habitual physical activity. 15,16 The appropriate clinical response to excess weight gain in ALL is unclear: while prevention of obesity is more effective than treatment, and is possible in childhood, 3 it is uncertain whether the focus of prevention should be on patients with ALL deemed to be at particularly`high risk' of developing obesity, or on all patients treated for ALL.…”
Section: Introductionmentioning
confidence: 99%